A Modern Musketeer Based on a Short Story by E.P. Lyle Jr. - Sauer, Rodney; Lyle, E. P. jr (Douglas Fairbanks: A Modern Musketeer, 2008)
Douglas Fairbanks Sr. stars as Ned Thacker, who is born during a Kansas cyclone and is thus imbued with the spirit of adventure. Having been virtually weaned on Alexandre Dumas' novel "The Three Musketeers", Ned grows up dedicated to old-fashioned chivalry. Alas, his well-meaning efforts to emulate his Musketeer idols nearly always backfire in a hilariously disastrous fashion. Ultimately, however, he is afforded an opportunity to rescue heroine Dorothy Moran in a true D'Artagnan-like manner. Unfortunately, only the first three reels of "A Modern Musketeer" are known to exist. Happily, however, this fragment includes a delightful dream sequence in which Fairbanks imagines himself to be a 16th-century swashbuckler - a fascinating (and arguably more enjoyable) precursor to his own 1921 screen version of "The Three Musketeers". [www.rottentomatoes.com]